(untitled) (Research Bulletins of the Faculty of Economic Sciences, 2017)
The article presents the essence and diversity of the taxation of local taxes and analyzed the height of tax revenues of municipalities with tax revenue in the Middle Pomerania in 2010-2014. Territorial structure of the region and the type determines the amount of revenues from income tax and has influence on the height achieved income. Character of local taxes can in most cases to predict possible to obtain the proceeds of this source of income.